RESEARCH OF EUPHEMISMS IN WORLD LINGUISTICS. THE CONCEPT OF WOMEN IN EVEMISMS - Yulchieva Zukhra Ummatkul kizi (Journals Park Publishing, 2023)
In this article, the essence of the phenomenon of euphemism in world linguistic culture, the definitions given by scientists, and the study of euphemisms by world linguists are given. Euphemisms representing the concept of woman are also discussed.
Keywords: euphemism, taboo, euphemism, language problems, semantic category, woman, concept, linguistic culture.